Pediatric Endocrinology in the Time of COVID-19: Considerations for the Rapid Implementation of Telemedicine and Management of Pediatric Endocrine Conditions - Regelmann, Molly O. (Horm Res Paediatr, 2021)
BACKGROUND: Pediatric endocrine practices had to rapidly transition to telemedicine care at the onset of the novel coronavirus disease 2019 (COVID-19) pandemic. For many, it was an abrupt introduction to providing virtual healthcare, with concerns related to quality of patient care, patient privacy, productivity, and compensation, as workflows had to change. SUMMARY: The review summarizes the common adaptations for telemedicine during the pandemic with respect to the practice of pediatric endocrinology and discusses the benefits and potential barriers to telemedicine. KEY MESSAGES: With adjustments to practice, telemedicine has allowed providers to deliver care to their patients during the COVID-19 pandemic. The broader implementation of telemedicine in pediatric endocrinology practice has the potential for expanding patient access. Research assessing the impact of telemedicine on patient care outcomes in those with pediatric endocrinology conditions will be necessary to justify its continued use beyond the COVID-19 pandemic.